The Influence of Using TikTok as a Learning Resource on Students’ Learning Outcomes in Fiqh Subject among Seventh Grade Students at MTsN 1 Buol - Nurul Aviva; Najamuddin Petta Solong; Apriliyanus Rakhmadi Pratama; Rendy S. Sambara (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This study examined differences in students' Fiqh learning outcomes before and after using TikTok as a learning resource and tested whether the intervention significantly affected seventh-grade students at MTsN 1 Buol. A quantitative quasi-experimental method with a nonequivalent control group design was applied. The sample consisted of class VII.C as the experimental group (n = 32) and class VII.D as the control group (n = 32), selected purposively because both classes used the same curriculum, studied the same topic, were taught by the same teacher, and were not acceleration classes. The intervention was conducted in four regular Fiqh meetings; TikTok was used as a supervised short-form microlearning resource through teacher-curated videos, guided worksheets, and group discussion. The instrument was a 24-item multiple-choice test that met validity and reliability criteria (KR-20 = 0.872). Descriptive results showed that the experimental class increased from 44.88 to 68.78, while the control class increased from 45.50 to 62.97. The independent-samples t-test indicated a significant difference in posttest scores (Sig. = 0.034 < 0.05; Cohen's d = 0.54). These findings indicate that TikTok, when curated and controlled pedagogically, can transform procedural Fiqh material into concrete audiovisual learning experiences. The study recommends TikTok as a complementary learning resource, provided that teachers apply content selection, digital discipline rules, and reflective discussion to minimize distraction.